Backyards and Butterflies Ways to Include Children with Disabilities in Outdoor Activities - Greenstein, Doreen ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
This sourcebook is designed for children, parents, and families, detailing ideas for outdoor play and learning activities, with emphasis on involving children with disabilities in outdoor play. A rural perspective permeates the guide, although each chapter contains ideas for making outdoor environments more accessible and safer for all children, in urban and rural settings. Safety messages are included throughout the book. The outdoor play ideas are intended as starting points to be changed around special family needs. The activity categories are: (1) garden; (2) nature; (3) animals; (4) wheels; (5) swings and slides; (6) backyard; and (7) measurements and materials, including balls, bolts, buckets, dowels, glues, handles/knobs, lumber/plywood, plastic, tie wraps, and Velcro. Illustrations of children involved in outdoor activities are included throughout. (BGC).
Availability: Brookline Books, P.O. Box 1047, Cambridge, MA 02238 ($14.95).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activities; Child Rearing; Disabilities; Early Childhood Education; Family (Sociological Unit); Gardening; Learning Activities; Outdoor Activities; Outdoor Education; Play; Recreational Activities; Rural Education; Rural Environment; Special Needs Students; Young Children; Outdoor Recreation; Books; Guides, Non-Classroom.